Indonesian EFL Learners' Ability to Comprehend and Produce Implicature - Widya Caterine; Tasya Amalia; Shafira Ghoni Rosyida Shaberina (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
To achieve a successful course of communication, one must master pragmatics, the study of context. To be able to have a proficient pragmatic competence, as one of macrolinguistics’ fields, getting acquainted with the target language’s cultural background is a must for foreign language learners. In a situation where someone is offered something, Indonesia has its own culture where the polite way to respond is to not directly accept or refuse the offer. This is actually considered as using implicature, one of the subfields of pragmatics. According to Stanford Encyclopedia of Philosophy (2019), implicature can be defined as the act of implying meaning by saying something else. The aim of using implicature is to mislead a response without lying while also maintaining a good social interaction. The objective of this study is to identify if EFL learners are capable of comprehending and producing implicature, one of pragmatics subfields or not. The method used in this study is descriptive qualitative research. The data were collected through assigning questionnaires and doing interviews on Brawijaya University students. The result of the study shows how most students are able to comprehend and produce implicature in English. The type of implicature they used was conversational implicature, one of the principal subjects of pragmatics.